Efficiency And Effectiveness Of Circuit Arrangement And Placement Of Thermoelectric For The Design Of Utilizing Zinc Roof As An Electrical Source - Sitti Maryam A. T. Arsyad; Asri Arbie; Abdul Wahidin Nuayi (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2024)
The problem related to electrical power sources commonly encountered in society is the frequent occurrence of rotating power outages or sudden blackouts, which disrupt activities for both communities and industries as they heavily rely on electrical power to meet their needs, both collectively and individually. In order to meet the needs of society and industry, Indonesia requires a sufficiently large energy supply. One renewable energy source that can be utilized is solar energy due to its easy availability, cleanliness, and cost-effectiveness. In this study, an experimental method is employed, which utilizes the heat from zinc roofs and converts it into electrical energy using thermoelectric generators. Testing is conducted by varying the circuit arrangements, including series, parallel, and combined configurations, as well as the number of thermoelectric modules (20, 30, and 42 modules), and placement locations on zinc roofs and house ceilings, to observe the output results in terms of voltage and electrical current. As observed from the test results presented in the graphs, the output voltage and current vary for each type of circuit. Based on the use of various circuit arrangements, it can be concluded that combining thermoelectric generators results in higher current and voltage values. The greater the number of thermoelectric modules, the larger the output value. There is a difference in output values between placement on zinc roofs and ceilings, with higher output values observed when installed on zinc roofs. This is due to direct contact between the hot side of the thermoelectric generator and the inner part of the zinc roof. All data obtained from these variations depend on the temperature difference between the hot and cold sides of the thermoelectric generator. The greater the temperature difference produced, the larger the voltage and current output from the circuit. This temperature difference affects the overall performance of the circuit.